Grammar Correction in AI-Assisted Business English Writing Instruction - Fahrur Rozi; Gina Larasty; Sri Wahyuni; Christianti Tri Hapsari; Lulu April Farida; Andy Sutrisno; Yolinda Pramudanti; Amelia Widihastutik; Amrina Rosyada (Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the efficacy of an AI-driven feedback tool in enhancing business English writing skills among higher education students. The research investigated 50 students' perceptions of the tool's advantages and its effectiveness in addressing specific issues in grammar, vocabulary, document organization, and genre conventions in business writing. The investigation employed a mixed-methods explanatory sequential design, integrating a five-point Likert questionnaire to assess learner attitudes and semi-structured interviews to investigate experiences in depth. The analysis employed a thematic approach to discern trends in perceived enhancement, efficiency, confidence, organizational support, and contextual direction. Research indicated that AI-generated feedback improves both mechanical and advanced writing skills, fosters learner independence, and reduces writing anxiety. These findings highlight the importance of integrating this technology into English for Specific Purposes programs to promote professional-quality writing in commercial contexts. Future researchers should explore the long-term effects of AI-driven feedback tools across diverse ESP contexts and compare the efficacy of multiple AI writing platforms in developing professional writing competence.